(untitled) (Journal of Hama University, 2024)
This research aimed to recognizing the effective of using Learning Package in Teaching Science on the achievement Of The Basic Fourth Grade Pupils In Hama Governorate, the study experimental method adopted to achieve objectives of the research were used achievement test consisting of 30 items, and the research sample consisting of (87) students, were divided into two groups: a control group (42) and the experimental group (45), and the most important results of the research: 1. There are differences statistically significant at the level of significance (0.05) between average degrees of the experimental group students and the average degrees of the control group students in the post- achievement test due to the learning technique variable. 2. There are differences statistically significant at the level of significance (0.05) between the average degrees of the experimental group students in the post- achievement test due to gender variable (male / female), interaction between the teaching technique and gender.